2021
DOI: 10.1080/09500693.2021.1953186
|View full text |Cite
|
Sign up to set email alerts
|

Why and how teachers make use of drawing activities in early childhood science education

Abstract: Researchers have provided many arguments for why drawing may contribute to science learning. However, little is known about how teachers in early childhood education (ECE) make use of drawing for science learning purposes. This article examines how teachers' views and framing of drawing activities influence the science learning opportunities afforded to children in the activities. We use activity theory to analyse teacher interviews and observation data from ten science classrooms (children aged 3-8 years) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…In respect to the drawing strategy, several studies have analysed the use of drawings related to teachers' beliefs and practice. Areljung et al (2021a) have examined 45 science class sessions of 11 early childhood and primary school teachers in Sweden, focusing on the 15 sessions in which the children drew pictures. These researchers have found that the teachers' beliefs about the role of drawing in science learning seems to be a key factor in enabling children to benefit from the pedagogical potential of drawing for learning science.…”
Section: Teachers' Readiness To Use Drawings As a Science Teaching St...mentioning
confidence: 99%
See 3 more Smart Citations
“…In respect to the drawing strategy, several studies have analysed the use of drawings related to teachers' beliefs and practice. Areljung et al (2021a) have examined 45 science class sessions of 11 early childhood and primary school teachers in Sweden, focusing on the 15 sessions in which the children drew pictures. These researchers have found that the teachers' beliefs about the role of drawing in science learning seems to be a key factor in enabling children to benefit from the pedagogical potential of drawing for learning science.…”
Section: Teachers' Readiness To Use Drawings As a Science Teaching St...mentioning
confidence: 99%
“…With respect to the other dimensions, all PSTs were aware of the usefulness of drawing as a teaching strategy and almost all of them were aware of its importance. These overall positive beliefs could have a beneficial effect on teachers' practice (Areljung et al, 2021a;Vartuli, 2005). Regarding confidence, in contrast, only one quarter of the PSTs showed a high level of confidence.…”
Section: Psts' Readiness For Using Drawings As a Science Teaching Str...mentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing enables children to channel various kinds of their imaginations that are expressed into drawings; from their drawings can be known the level of creativity and mood of each child (Papadopoulos, 2020). According to Areljung et al (2021), the steps in the drawing are: a) the teacher prepares everything that will be used in the drawing, both the tools and materials; b) The teacher gives an explanation of the activities to be carried out; c) Then the teacher gives opportunities to students in carrying out drawing activities; d) The teacher in supervising the protégé should not command or arrange the drawings made by the protégé; e) Children are given the freedom to express themselves by using materials that the teacher has prepared; f) After the specified time is over, the teacher collects the drawings of the students followed by a question and answer about the drawings that have been made. This research was carried out to see the improvement of children's creative abilities by providing children with drawing activities so that it can be a solution to problems in developing children's creativity in kindergarten.…”
Section: Introductionmentioning
confidence: 99%